Comparison of various treatments in diaper rash. - Ruggiero, G.; Ferrara, M.; Russomando, M.; D’Agostino, E.; D’Amato, N. (European Journal of Pediatric Dermatology, 2008)
Diaper rash is an irritant contact dermatitis, due to the prolonged contact with urine and feces, caused by the diaper. Bacterial and mycotic agents, proliferating more easily in the inflamed skin, can deteriorate diaper rash. In this report the effectiveness of probiotic, disinfectant, antimicrobial and antimycotic agents was evaluated in 160 children with diaper rash. Antibiotic and antimycotic lotions prove to be more effective than anti-proteasis lotions.